MEASURING THE ECONOMIC EFFICIENCY AND TOTAL PRODUCTIVITY OF RESOURCE AND THE TECHNICAL CHANGE OF AGRICULTURAL COMPANIES IN IRAQ USING SFA AND DEA FOR THE PERIOD 2005-2017 - & Lafta, Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The research aims to measure the economic efficiency and technological change and the total productivity of resources using the parameter and non-parameter methods, for agricultural companies registered in the Iraqi stock exchange, the number of 6 companies for the period from 2005 to 2017 based on the hypothesis that the  agricultural companies do not achieve economic efficiency and does not control the management of its operations, and It may be technically efficient but the size of its operations is not optimal. From non-parametric methods, the data envelope analysis method was used. Using the DEAP program, the Middle East Company achieved the highest average technical and cost efficiency of 0.62 and 0.58, respectively. The Iraqi seed production company achieved the highest average efficiency of 0.66. Using Al- Malmquist Index, the National Company for Agricultural Production achieved the highest rate of change in the total productivity of resources and the highest change in the technical efficiency respectively 1.97 and 2.28, while the Modern company for agricultural production obtained the highest technological change averaging 1.14. A stochastic frontier analysis (SFA) technique was used; logarithmic TL function was estimated using FRONT software. The maximum likelihood method (ML) shows that the capital was increased by 1%, the value of production of companies will increase by 0.22% because it helps to take advantage of the advanced technology that these companies are supposed to work to localize and support the agricultural sector. The cross-elasticity between labor and capital was 0.67 which indicates the nature of the substitution relationship between the two items, because using the technology reduces the workers. The value of sigma-squared was 0.21.